Pengaruh Kecanduan Narkoba terhadap Dinamika Hubungan Pasangan dan Implementasi Konseling Gestalt untuk Meningkatkan Kesadaran Diri - Nuryono, Wiryo; Ratnasari, Devi; Yasinta, Siti Dwi; Firdaus, Wardah Rikza; Az-Zahra, Tazkia Aulia; Kumariaksy, Fhito Atma; Firdaus, Musyafa Dafa (Universitas Palangka Raya, 2025)
Drug addiction has a profound impact on the dynamics and harmony of intimate relationships, particularly in emotional, communicative, and psychological aspects. This study aims to explore the effects of drug addiction on couple relationship patterns and evaluate the effectiveness of Gestalt counseling in enhancing self-awareness. A qualitative approach with a case study method was used, involving a university student at Universitas Negeri Surabaya who experienced relationship disharmony due to a partner's history of drug abuse. Data were collected through observation, in-depth interviews, and documentation, and analyzed using the Miles and Huberman model. The findings revealed that drug addiction led to behavioral changes, emotional instability, and decreased interpersonal quality. Through Gestalt counseling, the counselee demonstrated increased self-awareness, acceptance of emotional experiences, and an improved ability to rebuild relationship balance. Techniques such as the empty-chair dialogue and positive affirmations were effective in facilitating emotional reflection and cognitive restructuring. In conclusion, Gestalt counseling is a relevant approach to support individuals affected by drug-related relational disruptions in achieving greater personal insight and restoring relationship harmony.